SOCIAL ACTIVISM ANALYSIS ON THE NEWS TIMELINE SERIES OF THE JAMBI DEVELOPMENT PROJECT - Ripa'i, Ahmad Rido'i A; Sundari, Cici; Elianda, Yunita; Effendi, Ghina Nabilah (Universitas Padjadjaran, 2025)
This study aims to analyze social activism in a series of news reports on development projects in Jambi Province for the 2023–2025 period, particularly the civil society response to the implementation of 12 priority programs of Governor Al-Haris in the Jambi Province RPJMD. The study uses an exploratory qualitative approach with a literature review method and is a normative research type. Data were collected from 65 news articles in ten local online media, namely benuanews.com, Jambi One, Jambi.bps.co.id, Jambiberita.com, JambiEkspose.id, Jambiprov.go.id, Jambisatu.id, Radarjambi.co.id, Realitajambi.com, and Tribunjambi.com using the N Capture technique and analyzed with NVivo 12 Plus. The results of the study indicate that social activism in Jambi Province is a civil society response to the gap between planning and implementation of regional development policies, with news dominated by critical narratives of government performance, this can be seen from the analysis results where 21% of the news was negative compared to 14% which was positive. Activism is dominated by student movements from Batanghari University, Jambi University, and Sultan Thaha Saifuddin State Islamic University (UIN) Jambi, which exercise social control through policy advocacy, budget oversight, and mobilizing public participation. Online media has proven to be a mediator between the government and civil society, as well as a platform for legitimizing regional development narratives. Normatively, student activism serves as a crucial social control mechanism in promoting transparency and accountability in local government.